Application of artificial intelligence-based technologies in the corporate industry: opportunities and challenges - Annielyn C. Ariola; Ma. Lordes Mikaela M. Abalos; Elaisha M. Andres; Hanna Beatriz B. Barrion; Mary Lourdes T. Caasi; Jessie I. Quierrez (Ifma Publishing, 2025)
This study tried to determine the application of artificial intelligence-based technologies (AI) in the corporate industry focusing on the opportunities and challenges encountered by administrative professionals in Metro Manila. Findings showed that AI-based technologies present significant opportunities which heighten knowledge, skills, productivity, and efficiency. However, it also presents significant challenges like adaptability and flexibility issues in the change of work practices. The study suggests that workplaces should provide a centralized and accessible knowledge database, establish a clear and transparent data policy, create a robust support system, and implement regular assessments of employee skills. With AI integration, administrative professionals will need to acquire higher-order skills such as critical thinking, decision-making, and AI management. Administrative roles will require expertise in terms of AI compliance, cyber-security and financial data interpretation. Educational institutions may also enhance their curriculum and program offerings by designing interdisciplinary AI courses that merge business administration with data science, ethics, and digital literacy.